Stress concentration factor (SCF) analysis of welded joints - Low, Xing Yi. (2012)
This Final Year Project (FYP) report presents the study of the behaviour of a simple tubular T-joint subjected to axial tensile load, in-plane bending load (IPB) and out-of-plane bending load (OPB) by using the finite element software package, ANSYS (Version 13). This effort has been established to estimate magnitudes of the peak hot spot stresses (HSS) at the brace/chord intersection and to determine the corresponding Stress Concentration Factors (SCFs). The SCFs for pure axial loading, pure in-plane and out-of-plane bending loading are calculated using finite element method (FEM) and compared to different parametric equations for SCF. Two extrapolation methods were carried out to study the difference in the peak HSS distributions around the brace/chord intersection, using the finite element analysis approach to calculate the SCF results. Also the locations of the peak hot spot stresses which are the critical points in fatigue life assessment have been predicted.